2022
DOI: 10.3390/biology11030413
|View full text |Cite
|
Sign up to set email alerts
|

Small but Mighty—Exosomes, Novel Intercellular Messengers in Neurodegeneration

Abstract: Exosomes of endosomal origin are one class of extracellular vesicles that are important in intercellular communication. Exosomes are released by all cells in our body and their cargo consisting of lipids, proteins and nucleic acids has a footprint reflective of their parental origin. The exosomal cargo has the power to modulate the physiology of recipient cells in the vicinity of the releasing cells or cells at a distance. Harnessing the potential of exosomes relies upon the purity of exosome preparation. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 256 publications
(294 reference statements)
1
18
0
Order By: Relevance
“…A previous study observed how the development of rat cortical neurons led to the secretion of exosomes containing GluA2/3 subunits of AMPARs ( 79 ). Similar patterns of exosome secretion were also observed in the differentiated neurons ( 80 ). A previous study indicated that exosomes derived from cortical neurons only bind to neurons and not to glial cells ( 81 ), suggesting that neuron-derived EVs (NEVs) mediate neuron-to-glioma communication indirectly.…”
Section: Neuronal Regulation In Glioma Progressionsupporting
confidence: 76%
See 1 more Smart Citation
“…A previous study observed how the development of rat cortical neurons led to the secretion of exosomes containing GluA2/3 subunits of AMPARs ( 79 ). Similar patterns of exosome secretion were also observed in the differentiated neurons ( 80 ). A previous study indicated that exosomes derived from cortical neurons only bind to neurons and not to glial cells ( 81 ), suggesting that neuron-derived EVs (NEVs) mediate neuron-to-glioma communication indirectly.…”
Section: Neuronal Regulation In Glioma Progressionsupporting
confidence: 76%
“…A previous study indicated that exosomes derived from cortical neurons only bind to neurons and not to glial cells ( 81 ), suggesting that neuron-derived EVs (NEVs) mediate neuron-to-glioma communication indirectly. This indicated that the secretion of exosomes is activity-dependent and is specifically mediated by glutamatergic activity involving AMPAR and NMDAR ( 79 , 80 ). The glioma microenvironment renders neurons hyperexcitable due to the high glutamate concentration ( 67 ).…”
Section: Neuronal Regulation In Glioma Progressionmentioning
confidence: 99%
“…Exosomes are extracellular vesicles of 50–150 nm in diameter that are released by cells; they play an important role in intercellular communication and, thus, they circulate freely in body fluids, enter target cells, and may easily cross multiple anatomical and physiological boundaries, including the highly selective BBB [ 64 ]. They carry diverse molecular cargoes, such as nucleic acids (DNA, RNA, ncRNA, miRNA), lipids, and proteins that have a footprint reflective of their parental origin (both parent cells and extracellular environment) [ 65 , 66 ]. Compared to other substrates, the discovery of brain exosomes has been delayed.…”
Section: Resultsmentioning
confidence: 99%
“…No matter how the biogenesis of exosomes proceeds, they are composed of phospholipid bilayer structures that encapsulate lipids, proteins, and nucleic acids ( Kumari and Anji, 2022 ). Lipids, an essential part of exosome membrane, include cholesterol, sphingyelin, ceramide, etc.…”
Section: Exosomes and Exosomal Mirnasmentioning
confidence: 99%